Preparing for a Rainy Day: A Regulatory Focus Perspective on Job Insecurity and Proactive Career Behaviors - Lopez-Bohle, S (John Wiley and Sons Inc, 2025)
Previous research has primarily focused on how employees passively react to job insecurity (e.g., withdrawal). We shift this focus by examining when and for whom job insecurity may relate to proactive career behaviors. Leveraging regulatory focus theory and the diminishing marginal utility principle, we theorize a nonlinear moderated mediation model that links job insecurity to two proactive career behaviors — networking and seeking mentorship — through avoidance work motivation and depending on collectivism orientation. Two data sets, consisting of three-wave time-lagged surveys of employees from Chile and Australia, were used to examine our hypotheses. In both samples, for those high in collectivism orientation, job insecurity increased avoidance work motivation and subsequent proactive career behaviors up to a point, after which job insecurity was no longer related to these variables. For those low in collectivism orientation, regardless of the levels of job insecurity, there were no significant relations of job insecurity with avoidance motivation and subsequent proactive career behaviors in the Australian sample; however, the nonsignificant relations of job insecurity with avoidance motivation and subsequent proactive career behaviors turned positive in the Chilean sample. Overall, our research extends the job insecurity literature by demonstrating the conditions under which job insecurity increases proactive career behaviors. © 2025 The Author(s). Applied Psychology published by John Wiley & Sons Ltd on behalf of International Association of Applied Psychology.